Tenascin-C predicts IVIG non-responsiveness and coronary artery lesions in kawasaki disease in a Chinese cohort - Li, Yujie; Xu, Ziqing; Wu, Lin; Liang, Xuecun; Zhao, Lu; Liu, Fang; Wang, Feng (Frontiers in Pediatrics, 2022)
Objectives To assess the predictive value of tenascin-C (TN-C) for intravenous immunoglobulin (IVIG) non-responsiveness and coronary artery lesions (CALs) development at the acute stage of Kawasaki disease, and to build novel scoring systems for identifying IVIG non-responsiveness and CALs. Methods A total of 261 patients in acute-stage Kawasaki disease were included. Serum samples before IVIG initiation were collected and TN-C expression levels were measured using an enzyme-linked immunosorbent assay. In addition to TN-C, another fifteen clinical and laboratory parameters collected before treatment were compared between IVIG responsive and non-responsive groups, and between groups with and without CALs. Multiple logistic regression analyses were performed to construct new scoring systems for the prediction of IVIG non-responsiveness and CALs development. Results IVIG non-responsive group (n = 51) had significantly higher TN-C level compared to IVIG responsive group (n = 210) (15.44 vs. 12.38 IU/L, P < 0.001). A novel scoring system composed of TN-C, total bilirubin, serum sodium and albumin was established to predict IVIG non-responsiveness. Patients with a total score ≥ 2 points were classified as high-risk cases. With the sensitivity of 78.4% and specificity of 73.8%, the efficiency of our scoring system for predicting IVIG non-responsiveness was comparable to the Kobayashi system. Consistently, the group developing CALs at the acute stage (n = 42) had significantly higher TN-C level compared to the group without CALs (n = 219) (19.76 vs. 12.10 IU/L, P < 0.001). A new scoring system showed that patients with elevated TN-C, platelet count ≥ 450 × 109/L, and delayed initial infusion of IVIG had a higher risk of developing CALs. Individuals with a total score ≥ 3 points were classified as high-risk cases. The sensitivity and specificity of the novel simple system for predicting CALs development were 83.3% and 74.0%, respectively, yielding a better efficiency than the Harada score. Conclusion Elevated TN-C appeared to be an independent risk factor for both IVIG non-responsiveness and CALs in Chinese children with KD. Our scoring systems containing TN-C is simple and efficient in the early identification of high-risk KD cases that could benefit from more individualized medications.